2006
DOI: 10.1111/j.1475-097x.2006.00654.x
|View full text |Cite
|
Sign up to set email alerts
|

Differences in heart rate variability in non‐hypertensive diabetic patients correlate with the presence of underlying cerebrovascular disease

Abstract: We previously showed that diabetes contributes to the development of sclerotic lesions in cerebral arteries. In this study, we attempted to clarify whether differences in heart rate variability in non-hypertensive diabetic patients were dependent on the presence or absence of underlying cerebrovascular disease. Thirty diabetic subjects between 40 and 59 years of age and who had no prior history of hypertension were used in this study. Lacunar lesions (LA) were detected with magnetic resonance imaging and ather… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…In vivo studies have shown that heart rate variability is a significant risk factor in atherosclerosis [30, 31]. Our preliminary findings can lead us to speculate that, apart from the amplitude, the frequency may play an important role in VSMC phenotype alterations in the context of vascular diseases.In vivo, may be through protecting the contractile phenotype VSMCs against transforming to synthetic phenotype, lower heart ratesprevent the process of atherosclerosis, while higher heart rates accelerate its progression.…”
Section: Discussionmentioning
confidence: 79%
“…In vivo studies have shown that heart rate variability is a significant risk factor in atherosclerosis [30, 31]. Our preliminary findings can lead us to speculate that, apart from the amplitude, the frequency may play an important role in VSMC phenotype alterations in the context of vascular diseases.In vivo, may be through protecting the contractile phenotype VSMCs against transforming to synthetic phenotype, lower heart ratesprevent the process of atherosclerosis, while higher heart rates accelerate its progression.…”
Section: Discussionmentioning
confidence: 79%
“…Formations of atheromatous plaques result in atherosclerosis, including coronary atherosclerosis. Many studies have shown that atherosclerosis is significantly associated with decreased HRV 26 27 28 29 30 31. Particle exposure has been shown to influence plaque formation and stability 32.…”
mentioning
confidence: 99%
“…The present study excluded cardioembolic, undetermined and other determined subtypes because cardiac disease or undetermined disease may interfere with the validity of HRV analysis [12]. Some studies demonstrated that patients with LAC have higher sympathetic activity than control subjects [1,3]. A study by Dutsch et al on post-acute lacunar infarction patients showed stroke patients had lower HF and higher LF/HF [3].…”
Section: Discussionmentioning
confidence: 96%
“…However, the median time from stroke onset to recruitment was 31 months, and they also included subjects with a history of cardiac events and continued BP lowering agents. In a study by Nagata et al [1], diabetic patients with asymptomatic lacunar infarction had higher LF/HF than those without infarction. The present study included patients with LAC in the acute stage and demonstrated that their autonomic modulations were similar to those of control subjects.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation